Rancang Bangun Sistem Informasi Manajemen Jadwal Konsultasi Guru Bimbingan Dan Konseling Berbasis Web - Muh Ade Kurniawan; Raihan Alfarizi; Jhon Brian Tua; Army Trilidia Devega (Elkom: Jurnal Elektronika dan Komputer, 2026)
Guidance and Counseling (BK) services play a vital role in supporting students' academic, personal, social, and career development. However, at MA Darul Ihsan, scheduling counseling sessions is still done manually using logbooks, leading to time inefficiencies, difficulties in checking teacher availability, risks of data loss, and compromised student privacy. This research aims to design and implement a web-based information system for managing counseling schedules; this system enables students to submit and track requests online while assisting counselors and administrators in managing schedules, topics, and session approvals. The system was developed using the Waterfall methodology incorporating UML and ERD modelingand implemented using PHP, HTML, and MySQL. Key features include user login, schedule viewing, topic submission, and status tracking for students, alongside schedule and data management for administrators. Black-box testing confirmed that all primary features function as intended. The system is expected to make the scheduling process faster, more transparent, and more accessible than manual methods, although further development such as notification features and mobile accessibility support is still required.